On the Problems of Improvement the Article № 51 of the Civil Procedural Code of the Russian Federation - Evgeniy Fahraddinovich Rashidov; Yuriy Pavlovich Chulkov (Сибирское юридическое обозрение, 2012)
In this article is analyzed the procedural institute of a ban to be representative in the civil case, being realized concerning certain subjects of procedural legal relationships. The authors come to the conclusion about the necessity of its improvement by insertion of the corresponding additions into Article 51 of the Civil Procedural Code of the Russian Federation.